(3GdJOQjH h GKQg Ydi eSJhi GdNOeI GdebOeI ddYedGA HGdeUGQa GdJLGQjI HGdRGhjIs - (3gfjFI CHh HcQ(B, (3GdeOfjfjs ((3GdLRGFQ(B:s (3cfhR GdMceI(B,s, 2016)
(3eaGgje GdJOQjH, GdJOQjH h LhOI GdNOeGJ , GdJOQjH HGdeUGQa GdJLGQjI HGdRGhjI, JMdjd GdHjGfGJ h GdeYdheGJ h GdfJGFL h GdJhUjGJ(B.s
(3eQGLY U(B.179s
Keywords: (3GdHfhc GdJLGQjIs; (3GdJOQjHs